1982
DOI: 10.1111/j.1365-3024.1982.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of acquired host antigens during schistosome maturation

Abstract: Schistosomes grown in mice were tested at different stages of development for susceptibility to an in vitro cytotoxic effector mechanism involving eosinophils and an antibody directed against mouse determinants. Despite the fact that 5-day lung worms and 6-week adult worms both bound the antibody to their surfaces, eosinophils attached preferentially to the adults and killed them. Complement had an enhancing effect in this system. Those eosinophils which did adhere to the lung worms degranulated onto the tegum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 27 publications
3
65
1
Order By: Relevance
“…There is consensus, however, about the lungstage schistosomula being the main targets of natural and RA-mediated protective immunity (Coulson 1997). Paradoxically, no specific antibody is able to bind to lung-stage larvae surface membrane antigens, as judged by several serological tests, namely indirect membrane immunofluorescence (Dean 1977, Dessein et al 1981, McLaren and Terry 1982, Foley et al 1986, Pearce et al 1986, Chiang and Caulfield 1989, Kusel and Gordon 1989, Coulson 1997, 2004b, El Ridi and Tallima 2006, Kusel et al 2007). Entire failure of surface membrane antigen detection does not give support to the contention that the tegument is bounded externally by a single lipid bilayer, overlain by a laminate secretion containing numerous proteins and molecular complexes , and was previously ascribed to shedding of antigenic molecules (Pearce et al 1986), masking by host proteins Terry 1982, Chiang andCaulfield 1989), or intrinsic biochemical modifications of the outer membrane (Dean 1977, Dessein et al 1981, Foley et al 1986, Kusel and Gordon 1989, Kusel et al 2007).…”
Section: Schistosoma Mansoni Glyceraldehyde 3-phosphate Dehydrogenasementioning
confidence: 99%
“…There is consensus, however, about the lungstage schistosomula being the main targets of natural and RA-mediated protective immunity (Coulson 1997). Paradoxically, no specific antibody is able to bind to lung-stage larvae surface membrane antigens, as judged by several serological tests, namely indirect membrane immunofluorescence (Dean 1977, Dessein et al 1981, McLaren and Terry 1982, Foley et al 1986, Pearce et al 1986, Chiang and Caulfield 1989, Kusel and Gordon 1989, Coulson 1997, 2004b, El Ridi and Tallima 2006, Kusel et al 2007). Entire failure of surface membrane antigen detection does not give support to the contention that the tegument is bounded externally by a single lipid bilayer, overlain by a laminate secretion containing numerous proteins and molecular complexes , and was previously ascribed to shedding of antigenic molecules (Pearce et al 1986), masking by host proteins Terry 1982, Chiang andCaulfield 1989), or intrinsic biochemical modifications of the outer membrane (Dean 1977, Dessein et al 1981, Foley et al 1986, Kusel and Gordon 1989, Kusel et al 2007).…”
Section: Schistosoma Mansoni Glyceraldehyde 3-phosphate Dehydrogenasementioning
confidence: 99%
“…These dominant evasion strategies have been described as a system of mimicry capable of producing antigens that are similar to endogenous host components (2-4), antigen disguise through acquisition of host molecules to cover the outer worm surface (5,6), and immunological modulation through interference with host immune systems (7)(8)(9)(10). Among these strategies, schistosome excretory/secretory (ES) 1 products have been shown to elicit host immunological modulation functions (7,11).…”
mentioning
confidence: 99%
“…One of the mechanisms that have been proposed to account for the successful survival of the adult worm is the masking of parasite target epitopes by molecules from host origin, acquired during worm development (host antigen hypothesis) (2,3). In vitro studies have shown that schistosomula (schla) 1 in contact with host erythrocytes (E) acquire cell-derived antigens (4)(5)(6) and become resistant to immune attack (7).…”
mentioning
confidence: 99%